Tinjauan Yuridis Sosiologis Terhadap Pelaksanaan Perkawinan Dibawah Umur : (Studi Kasus Desa Owata, Kecamatan Bulango Ulu, Kabupaten Bone Bolango) - Nurmin K. Martam; Yayan Hanapi (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Underage marriage is a significant issue in various regions in Indonesia, including Owata Village, Bulango Ulu Subdistrict, Bone Bolango Regency. This study aims to examine the implementation of underage marriage from a juridical and sociological perspective. A qualitative approach with descriptive methods was used to understand the social, cultural, economic and educational factors that influence the phenomenon. The results show that the main factors that encourage early marriage include deep-rooted social norms and traditions, economic pressure, low access to education, and lack of understanding of the legal and health impacts. This practice often contradicts Law No. 16/2019, which sets the minimum age of marriage at 19 years. The consequences of underage marriage include negative impacts on reproductive health, increased risk of domestic violence, and barriers to education and careers. Therefore, comprehensive efforts through community education, economic empowerment, increased legal socialization, and more effective supervision are needed to reduce the practice of early marriage and protect children's rights. This research emphasizes the importance of synergy between the community, legal apparatus, and government to provide sustainable solutions.